2019
DOI: 10.3390/geosciences9030144
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Remotely Sensed Soil Moisture for Temporal and Spatial Analysis of Rainfall over São Francisco River Basin, Brazil

Abstract: Variability in precipitation patterns in the northeast and southeast regions of Brazil are complex, and the combined effects of the Tropical Atlantic, Pacific Niños, and local characteristics influence the precipitation rates. This study assesses the performance of multi-satellite precipitation product SM2RAIN-Climate Change Initiative (SM2RAIN-CCI) for the period of 1998–2015 at monthly scale. To accomplish this aim, various statistical analyses and comparison of multi-satellite precipitation analysis product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Paredes-Trejo et al [30] showed that for the NEB, this product provides the best performance in terms of Pearson correlations over the Cerrado biome, but fails in the estimation of the amount of rainfall under extreme moisture conditions. Souto et al [42] presented similar results for the São Francisco River basin in Brazil.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Paredes-Trejo et al [30] showed that for the NEB, this product provides the best performance in terms of Pearson correlations over the Cerrado biome, but fails in the estimation of the amount of rainfall under extreme moisture conditions. Souto et al [42] presented similar results for the São Francisco River basin in Brazil.…”
Section: Introductionmentioning
confidence: 63%
“…Larger biases in these SPPs were evident over inland northeast Brazil and on the eastern part of the Chapada Diamantina and Serra do Espinhaço cordilleras, in particular for SM2RAIN-ASCAT in summer and autumn (Figure 6j-l). In these regions, the impact of topographic complexity (see Figure 1c) and volume scattering in dry soils [71] on soil moisture retrieval accuracy has been well documented and extensively analyzed in the literature [42,[85][86][87]. A factor less evident that influenced the numerical performance of both SM2RAIN-based products in term of bias is linked to the fact that the rainfall in summer is characterized by intense and short rainfall events (excepting the PMP biome) [88].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the interest of the product developers (Brocca et al, 2019), the SM2RAIN P-datasets reliability has only been systematically reported in India (Prakash, 2019), Brazil (Paredes-Trejo et al, 2019;Souto et al, 2019), Pakistan (Rahman et al, 2019), West Africa (Satgé et al, 2020), Austria (Sharifi et al, 2019) and China (Zhang et al, 2019). These studies used precipitation gauge observations as a reference to assess the potential benefits of the SM2RAIN P-datasets ('bottom-up' approach) compared to well-established state-of-the art SPPs.…”
Section: Opportunities and Limitations Of Available Sppsmentioning
confidence: 99%
“…Similarly, Souto et al . (2019) reported that approximately 69.0% of the SFW extension presents a decreasing trend in annual rainfall, although no statistical significance was found. Additionally, Mutti et al .…”
Section: Discussionmentioning
confidence: 97%